Portuguese Emerging Art : PEAC2017. - Ambrósio, Daniela; Caeiro, Mário; Quintas, Rudolfo; Camacho, Cláudia; Reis, Jorge; Lockhart Nelson, Simeon; Santos, Luísa (Torres Vedras : EMERGE, 2017)
de Pinho, Alexandra ; Gonçalves, Alice Joana ; Alma d'Africa ; Velez, Ana ; Wever, Ana ; Banha, André ; Catarina, André ; Martins, André ; Silva, André ; Ferreira, António G. ; Santos, Benedita ; Castro Santos, Bruno ; Lavos Marques, Bruno ; Rebelo, Carla ; Grilo Santos, Carolina ; Rocha, Carolina ; Nunes, Catarina ; Alfacinha, Daniel ; Gonçalves, David ; Rosado, David ; Esperança, Débora ; Viegas, Diogo ; Artur, Eunice ; Garcia, Filipe ; Birra, Gonçalo ; Brites, Inês ; Norton, Inês ; Teles, Inês ; Falcão, Joana ; Abreu Valente, João ; Biscainho, João ; Cristóvão Leitão, João ; Ferreira, João R. ; Saramago, João ; Américo, Jorge ; Fonseca, Leonor ; Valente Pereira, Lucy ; Almeida, Luís ; Plácido Costa, Luís ; Passos, Luísa ; Champalimaud, Maísa ; Carvalho, Márcio ; Menescal, Dantas, Marcelo ; Cruz Correia, Maria Lúcia ; Dias Coutinho, Mariana ; Duvall, Nádia ; Alexandre, Nuno ; Geraldes, Patrícia ; Prates, Paula ; Sousa, Paulo ; Oliveira, Pedro ; Rainho, Rita ; Roda, Sandra ; Verdade, Tiago ; Pereira, Vieira
boek